The significance of Fas, tumor necrosis factor-related apoptosis-inducing ligand and fibrinolytic factors in the assessment of malignant pleural effusion - Choi, Jong Weon; Lee, Moon Hee; Fujii, Tatsuyoshi (Archives of Biological Sciences, 2022)
Paper description: Pleural effusion occurs as a complication of different diseases, resulting from a disruption in pleural homeostasis and increased pleural permeability. Patients with pleural effusion were evaluated by measuring Fas, tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), tissue-type plasminogen activator (tPA), plasminogen activator inhibitor-1 (PAI-1), D-dimers, and lactate dehydrogenase (LD). Fas and TRAIL levels were significantly higher in malignant pleural effusion, and Fas had a significantly higher ability to identify malignant effusion than tPA and LD. Fas was positively correlated with tPA and D-dimers, but not with biochemical parameters. These results contribute to evaluations of patients with suspected malignant pleural effusion. Abstract: Few studies have examined the usefulness of soluble apoptotic markers for the screening of pleural effusion. This study aimed to investigate the significance of Fas, tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) and fibrinolytic factors for the assessment of patients with malignant pleural effusion. A total of 137 patients with pleural effusion were evaluated. Soluble Fas, TRAIL, tissue-type plasminogen activator (tPA), plasminogen activator inhibitor-1 (PAI-1), D-dimers and lactate dehydrogenase (LD) levels were measured. Pleural fluid/blood ratios (P/B) of fibrinolytic factors were calculated. Fas and TRAIL levels were significantly higher in patients with malignant effusion than in those with non-malignant effusion. Malignant effusion was 1.6-fold more prevalent in patients with elevated Fas than in those without (48.5% vs 30.4%, P=0.031). The P/B ratio of tPA was 2.5-fold higher in malignant effusion than in non-malignant effusion (4.65 vs 1.83, P<0.001). Fas was positively correlated with tPA and D-dimers, but not with biochemical parameters. The ability of Fas to identify malignant effusions was significantly greater than those of tPA and LD. In conclusion, measurements of Fas and TRAIL in conjunction with fibrinolytic factors may provide information useful for monitoring patients with suspected malignant pleural effusion.